The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1999
DOI: 10.1002/(sici)1520-6688(199924)18:1<28::aid-pam3>3.0.co;2-a
|View full text |Cite
|
Sign up to set email alerts
|

The effect of disabilities on exits from AFDC

Abstract: The Personal Responsibility and Work Opportunity Reconciliation Act (PRWORA) of 1996 replaces AFDC, the largest means‐tested cash assistance program for low‐income families, with the Temporary Assistance for Needy Families (TANF) block grant. Unlike AFDC, assistance under TANF is limited to five years in a lifetime, and states are required to move families from the assistance rolls into jobs. But not all adult welfare recipients can easily move to work because either they themselves are disabled or they have a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 8 publications
3
21
0
Order By: Relevance
“…Women who are married were more likely to leave welfare (Harris, 1996;Meyer and Cancian, 1996;Leahy et al, 1995). Older women tend to spend less time on welfare (Plotnick, 1983;Acs and LoPrest, 1999). Freeman (1998) suggests that although life-cycle factors may be important in predicting moves out of public housing, cultural or rational choice explanations are more important when all are included in a single explanatory model.…”
Section: Who Leaves Public Housing?supporting
confidence: 82%
See 1 more Smart Citation
“…Women who are married were more likely to leave welfare (Harris, 1996;Meyer and Cancian, 1996;Leahy et al, 1995). Older women tend to spend less time on welfare (Plotnick, 1983;Acs and LoPrest, 1999). Freeman (1998) suggests that although life-cycle factors may be important in predicting moves out of public housing, cultural or rational choice explanations are more important when all are included in a single explanatory model.…”
Section: Who Leaves Public Housing?supporting
confidence: 82%
“…Exits from welfare are more likely to occur among those who have a previous work history (O'Neill et al, 1987;Kimenyi, 1991) and some attachment to the labor force during their time on welfare (Harris, 1996;Kimenyi, 1991;O'Neill et al, 1987). Welfare exits are less likely to occur among those with no high-school diploma (Leahy et al, 1995;Acs and LoPrest, 1999;Seninger, 1998). For public and assisted housing, the impact of education is mixed (Hungerford, 1996;Freeman, 1998).…”
Section: Who Leaves Public Housing?mentioning
confidence: 99%
“…Some past studies showed associations between having a child with a disability and reduced parental employment (Kuhlthau and Perrin 2001;Thyen, Kuhlthau, and Perrin 1999;Hill 1993, 1995) and another study found that availability of child care influenced the mother's decision to quit a job (Acs and Loprest 1999). This study supported those findings.…”
Section: Discussionmentioning
confidence: 99%
“…The literature indicated a high prevalence of child disability among low-income families and that many families receiving government assistance had at least one child with a disability or chronic health problem (Acs and Loprest 1999;Lukemeyer, Meyers, and Smeeding 2000).…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation